2014
DOI: 10.1007/s10880-014-9406-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Health-Related Quality of Life over Time Among Adolescents and Young Adults with Sickle Cell Disease

Abstract: Little is known about what factors affect the health-related quality of life (HRQoL) of adolescents and young adults (AYAs) with sickle cell disease (SCD), and how their HRQoL changes over time. This retrospective study included 87 AYAs attending a SCD Adolescent Clinic who completed a measure of HRQoL at each visit over the course of approximately 1.3 years. Results suggested that the following were associated with poorer physical HRQoL: being female, more healthcare utilization events, and presence of intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…A retrospective study suggested that poorer physical HRQoL domains were significantly correlated to more healthcare utilization events [42]. Our unadjusted analyses confirmed these findings: all dimensions of HRQoL were found to be predictors of high rates of SCD-related ED visits except emotional well-being.…”
Section: Discussionsupporting
confidence: 82%
“…A retrospective study suggested that poorer physical HRQoL domains were significantly correlated to more healthcare utilization events [42]. Our unadjusted analyses confirmed these findings: all dimensions of HRQoL were found to be predictors of high rates of SCD-related ED visits except emotional well-being.…”
Section: Discussionsupporting
confidence: 82%
“…A large body of literature has investigated the quality of life of this population (Barakat, Patterson, Daniel, & Dampier, 2008;Jackson, Lemanek, Clough-Paabo, & Rhodes, 2014;Menezes, Len, Hil ario, Terreri &, Braga, 2013). An earlier study observed that children and adolescents with SCD spend most of their time enduring the chronic and acute pain events at home, tend to underreport their pain levels, and tend to dismiss the negative effects of SCD on their daily lives (Fuggle, Shand, Gill, & Davies et al, 1996).…”
Section: Quality Of Life In Children With Scdmentioning
confidence: 99%
“…The treatment of TM requires lifelong red cell transfusion support with consequent iron overload, especially in the absence of optimal and lifelong iron chelation therapy, in addition to other hazards of transfusions. Collectively, these complications result in a deteriorating quality of life (QOL) and function in affected individuals with both disorders .…”
Section: Introductionmentioning
confidence: 99%